Peripheral service quality, satisfaction and intent to return among tourists attending sports event: a case of Melaka Century Ride 2015 / Muhammad Aliff Haiqal Hamdzah, Muhammad Syazrin Md Yazid and Muhamad Razi Mustar - Hamdzah, Muhammad Aliff Haiqal; Md Yazid, Muhammad Syazrin; Mustar, Muhamad Razi (2015)
The primary purposes of this study were to: a) to examine the satisfaction of attendees based on peripheral service quality at Melak:a Century Ride 2015; and b) to investigate the relationship of satisfaction and intention to participate in the future Melaka Century Ride 2015. This research intends to explore the participants satisfaction and their future intention at MCR 2015 by quantifying perceived assessments using proposed model suggested by Tsuji, Bennet and Zhang. In order to answer the issues related to the main objectives, the following research question are develop: a) to what extent attendees is satisfied with peripheral service quality at MCR 2015? b) is there any relationship between participant satisfaction and future intention to participate in future MCR 2015? A secondary purpose of the study was to develop a scale to measure service quality in selected dimensions, participant satisfaction and future intentions. The model was tested using data collected from participants at the Melaka Century Ride 2015.